A Randomized, Prospective and Crossover Study, Comparing the Eradication Rate After 10 Days of Concomitant Therapy to Bismuth Quadruple Therapy Among a Sample of the Lebanese Population - Jad Chidiac, MD; Reine-Marie Kahwaji, MD; Souheil Hallit, PharmD, MSc, MPH, PhD; Yara Yazbeck, MD; Bassem Akiki, MD; Charbel Yazbeck, MD (Current Therapeutic Research)
ABSTRACT: Background: Concomitant therapy and bismuth quadruple therapy are both recommended as first-line treatment regimens for the empiric treatment of Helicobacter pylori infection, especially after the increased resistance to clarithromycin. Objective: Our goal was to compare both treatment regimens among a sample of the Lebanese population to eventually conclude whether one of these therapies has a higher efficacy than the other one as a first- and second-line treatment regimens. Methods: It is a randomized, prospective, and crossover study, started from March 2016 to December 2018. Participants were randomly chosen patients diagnosed with active H pylori through histology. Two groups were then formed randomly and equally: patients in the first group received 10 days of concomitant therapy, whereas patients in the second group received 10 days of bismuth quadruple therapy. Eradication was evaluated by the 14C urea breath test done 6 weeks after the end of antibiotic use. A negative breath test indicated a successful eradication. All patients with a positive breath test were then given the other treatment regimen for another 10 days and then re-evaluated for eradication in the same manner. Results: Both regimens demonstrated similar efficacy as first-line therapies for H pylori eradication. Among 175 patients receiving concomitant therapy, 160 (91.4%) achieved eradication, whereas in the 174 patients treated with bismuth quadruple therapy, 164 (94.2%) were successfully eradicated (P = 0.306). Among patients requiring second-line treatment, 14 of 15 (93.3%) who failed concomitant therapy were successfully treated with bismuth quadruple therapy, whereas all 10 patients (100%) who failed bismuth therapy achieved eradication with concomitant therapy (P < 0.001). Conclusions: Bismuth quadruple therapy and concomitant therapy are both equally effective first-line treatment regimens for the eradication of H pylori. They are also effective if used as second-line treatment regimens for this purpose. Lebanese Clinical Trials Registry identifier: LBCTR2024095653.